Technical note: A comparison of methods for estimating coccolith mass - C. R. Valença; L. Beaufort; G. M. Hallegraeff; M. N. Müller; M. N. Müller (Biogeosciences, 2024)
The fossil record of coccolithophores dates back approximately 225 million years, and the production of their calcite platelets (coccoliths) contributes to the global carbon cycle over short and geological timescales. Variations in coccolithophore parameters (e.g. community composition, morphology, size and coccolith mass) are a key factor for ocean biogeochemical dynamics (e.g. biological carbon pump) and have been used as a palaeoproxy to understand past oceanographic conditions. Coccolith mass has been frequently estimated with different methods with electron microscopy being the most applied. Here, we compared the electron microscopy (EM) method with the Coulter multisizer (CM) (i.e. electric field disturbance) and bidirectional circular polarization (BCP) methods to estimate coccolith masses (pg CaCO3) in controlled laboratory experiments with two ecotypes of Emiliania huxleyi. Average coccolith mass estimates were in good agreement with literature data. However, mass estimates from the CM were slightly overestimated compared to EM and BCP estimates, and a correction factor (cf=0.8) is suggested to compensate for this discrepancy. The relative change in coccolith mass triggered by morphotype-specific structures and environmental parameters (i.e. seawater carbonate chemistry) was suitably captured by each of the three techniques.